(untitled) (Actualizaciones en Sida e Infectología, 2024)
This clinical case details a patient with advanced HIV who developed disseminated Kaposi sarcoma (KS), affecting skin, mucous membranes, lung, liver and other organs. The objective was to document the clinical complexity and fatal complications of this neoplasm associated with severe immunosuppression. The patient presented extensive skin and visceral lesions, with a CT scan revealing pulmonary infiltrates and nodules in several organs, confirmed by biopsies as KS with anomalous vascular proliferation. The discussion highlights that advanced immunosuppression, exacerbated by a recent COVID-19 infection, facilitated the rapid progression of KS. This case highlights the need for early intervention with antiretroviral therapy and proper management of KS. In conclusion, late management of HIV and KS significantly limits therapeutic options and generally leads to a fatal outcome, highlighting the importance of timely diagnostic and therapeutic strategies to prevent aggressive evolution in immunosuppressed patients.